Preferensi Hijauan Pakan Gajah Sumatera (Elephas maximus sumatranus): Studi Kasus di Kawasan Seblat - Syarifuddin, Hutwan (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The    research    has    purposed  were  to  know forages of  the  gajah  Sumatera    (Elephas  maximus sumatranus)  preference.  Data  primer    was  calculated  with    direct  method  in  field  with    vegetation analysis.  The  result    showed    that most  fodder    types  were   Air  Tenang  (225).  Air  Senaba  and  Air Sabai  (215)  were similar.  Batu  Ampar    (213),  Simpang  Tiga    (207). Air  Riki  was lowest    (197).  The sum    of    elephant  forages  were in Air  Tenang    (70  types),  Air  Senaba  (67    types),  Simpang  Tiga  (66  types), Air Sabai (64 types), Air  Riki (63   types)  and  Batu Ampar  (59   types). The forages type    was liked  as:  Colocasia  gigantea,  Imperata  cylindrica,  Cynodon  dactylon   and  Ichnanthus  vicinus, Angiopteris  avecta,   Knema  sp,  Macaranga  gigantea,  Macaranga  pruinosa, Parkia  speciosa,  Mallotus paniculatus, and  Arthocarpus elasticus.